Models for Solid Oxide Fuel Cell Systems Exploitation of Models Hierarchy for Industrial Design of Control and Diagnosis Strategies - Marra, Dario; Pianese, Cesare; Polverino, Pierpaolo; Sorrentino, Marco (Green Energy and Technology, 2016)
XXII, 154 p. 86 illus. in color.